Nutritional supplementation as a therapeutic approach in autistic spectrum disorder: A literature review - Ângelo, Kyvia Hellen de Araújo (2021)
Objective: Expose the relevance of identifying vitamin deficits in the autistic organism, inflammation resulting from this process, as well as the influence of vitamin nutritional supplementation for the development of a better quality of life for these children. Methodology: Literature review study, based on scientific articles indexed in virtual libraries: MEDLINE, LILACS, SCIELO and Google Scholar, conducted between January and February 2021, with the inclusion criteria: full papers in languages: Portuguese, English and Spanish, published in the last eight years and that addressed the issue in its entirety. Incomplete articles absent in databases and those subjects not supplied the purpose of this research were excluded. Results and discussion: From the fifteen articles analysis, it was found that multivitamin and mineral supplementation consisting of fundamental importance for the autism, given that the selectivity limits the variety of foods and generate nutritional deficiencies, stimulating calorie malnutrition above -protein. Conclusion: It appears that autistic individuals, with their difficulties based on this triad, need vitamin supplements based on omega-3, iron, D and B vitamins for a better quality of life, given the existence of a deficit high methylation that influences the effective absorption of food, triggering inflammations from the Central Nervous System.